2009
DOI: 10.1021/jf8031588
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora and Mycotoxin Production in Oilseed Cakes during Farm Storage

Abstract: Agricultural activities involve the use of oilseed cakes as a source of proteins for livestock. Because the storage of oilseed cakes could induce the development of molds and the production of mycotoxins, a survey was conducted during the 5 months of farm storage. Mycoflora was studied by microscopic examinations, and the presence of Aspergillus fumigatus was confirmed by polymerase chain reaction. A multimycotoxin method was developed to quantify seven mycotoxins (aflatoxin B(1), alternariol, fumonisin B(1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Alternariol, alternariol monomethyl ether, and tenuazonic acid were found in rapeseed and sunflower meals, but the consequences of these levels for pig and poultry health are difficult to establish [134,135]. Studies on mycoflora and mycotoxin production in oilseed cakes during on-farm storage suggested that toxinogenic strains of Aspergillus fumigatus can develop and produce gliotoxin [136]. Old studies on mustard and mustard products also suggested that toxinogenic strains of Fusarium oxysporum can grow on Brassicaceae and produce diaxetoxyscirpenol, T-2 toxin and zearalenone [137].…”
Section: Mycotoxin Contaminationmentioning
confidence: 99%
“…Alternariol, alternariol monomethyl ether, and tenuazonic acid were found in rapeseed and sunflower meals, but the consequences of these levels for pig and poultry health are difficult to establish [134,135]. Studies on mycoflora and mycotoxin production in oilseed cakes during on-farm storage suggested that toxinogenic strains of Aspergillus fumigatus can develop and produce gliotoxin [136]. Old studies on mustard and mustard products also suggested that toxinogenic strains of Fusarium oxysporum can grow on Brassicaceae and produce diaxetoxyscirpenol, T-2 toxin and zearalenone [137].…”
Section: Mycotoxin Contaminationmentioning
confidence: 99%
“…Other mycotoxins such as trichothecenes and zearalenone (ZEA) alter immune-mediated activities in bovines (Black et al, 1992). Occurrence of mycotoxins such as AFs, FBs, ZEA, T 2 toxin and gliotoxin in cattle feeds and ingredients has been already reported (Batatinha et al, 2007;Naicker et al, 2007;Simas et al, 2007;Lanier et al, 2009;Lanier et al, 2010). Simas et al, (2007) encountered Aspergillus spp, Penicillium spp and Fusarium spp, in brewer's grains samples intended for cattle.…”
Section: Introductionmentioning
confidence: 95%
“…The respiratory route has been recognized in the past two decades as an important route of exposure, especially for workers in corn storage facilities and in animal farms [ 9 , 10 , 11 ]. Indeed, some studies have established an association between low-level exposure to molds and mycotoxins, and asthma or chronic airway inflammation, especially among workers in an agricultural setting [ 9 , 12 ]. Such exposure is related to the onset of farmers’ lung disease [ 13 ], hypersensitivity pneumonia, and allergic bronchopulmonary aspergillosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%